2018
DOI: 10.1038/s41598-018-25101-8
|View full text |Cite|
|
Sign up to set email alerts
|

Artisanal shark fishing in Milne Bay Province, Papua New Guinea: biomass estimation from genetically identified shark and ray fins

Abstract: Our study is the first detailed examination of species composition using DNA COI barcoding of elasmobranchs from an artisanal fishery of Papua New Guinea. The study is the first in the region to provide biomass estimates based on species confirmation following examination of dried fins. Over 20 species of elasmobranchs were identified from 623 fins from the artisanal fishery in Milne Bay Province of PNG, with Carcharhinus amblyrhynchos and Carcharhinus melanopterus the most abundant species in the catches. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Hellberg, et al, 2019;Ward, Holmes, White, & Last, 2008). While the full-length DNA barcode can effectively differentiate many of these species (e.g., see Appleyard et al 2018;Wong et al 2009), the shorter amplicon generated with mini-barcoding showed reduced differentiation capability when relying on a distance-based approach. In some of these cases, the use of character-based identification keys developed in previous studies (Fields, et al, 2015;Velez-Zuazo, et al, 2015;Wong, et al, 2009) enabled differentiation (Table 4).…”
Section: Shark Mini-barcoding Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hellberg, et al, 2019;Ward, Holmes, White, & Last, 2008). While the full-length DNA barcode can effectively differentiate many of these species (e.g., see Appleyard et al 2018;Wong et al 2009), the shorter amplicon generated with mini-barcoding showed reduced differentiation capability when relying on a distance-based approach. In some of these cases, the use of character-based identification keys developed in previous studies (Fields, et al, 2015;Velez-Zuazo, et al, 2015;Wong, et al, 2009) enabled differentiation (Table 4).…”
Section: Shark Mini-barcoding Considerationsmentioning
confidence: 99%
“…DNA-based techniques, such as DNA barcoding and species-specific polymerase chain reaction (PCR), are commonly used to identify elasmobranch species when morphological indicators are lacking (Appleyard, White, Vieira, & Sabub, 2018;Dudgeon, et al, 2012;Hanner, Naaum, & Shivji, 2016;Rodrigues-Filho, Pinhal, Sondre, & Vallinoto, 2012). While species-specific PCR is preferable for targeted approaches, DNA barcoding is more appropriate for applications involving a wide range of species, such as shark cartilage supplements.…”
Section: Introductionmentioning
confidence: 99%
“…However, as in Belize, it is common for these fisheries to be highly skewed to a small number of Volume 35, No. 3, 2021 common species (e.g., Appleyard et al 2018), which in some cases could facilitate visual identification of most of the anal fins. The DNA testing could then be reserved for rarer types and ambiguities among common species.…”
Section: Discussionmentioning
confidence: 99%
“…Fishing practices may also need to be adapted as in the PNG longline fishery sharks are often electrocuted prior to landing to protect crew (Kumoru, 2003). Overlap with other fisheries must also be considered, as, using the PNG fishery as a further example, some of these species are also caught in trawl, gill net, purse seine and artisanal fisheries (Appleyard, White, Vieira, & Sabub, 2018; Nicol et al., 2009; Teh et al., 2014). The practices or selectivities of these other fisheries could undermine the harvest strategies outlined here.…”
Section: Discussionmentioning
confidence: 99%